A review of security assessment methodologies in industrial control systems - Qassim Q.S.; Jamil N.; Daud M.; Patel A.; Jaaffar N. (Emerald Group Holdings Ltd., 2023)
Computer crime; Crime; Network security; Power control; SCADA systems; Standby power systems; Cyber-attacks; Design/methodology/approach; Electrical power networks; Industrial control systems; Security assessment; Security vulnerabilities; Vulnerability analysis; Vulnerability assessments; Electric power system control